Assessment of Energy Poverty in New European Union Member States: The Case of Bulgaria, Croatia and Romania - Vlahinic Lenz, Nela; Grgurev, Ivana (International Journal of Energy Economics and Policy, 2017)
Energy poverty has become a rising issue in EU, especially in new Member States, but still there is no uniform methodology in defining energy poverty and policy measures. The aim of our paper is to assess and compare the number of energy poor households in three new EU Member States based on quantitative indicators like the number of energy poor households that use financial measures related to energy sector and the number of households that spend more than 10% of their income on energy. Our results show that the number of energy poor population increased in the period 2009-2014 in all three countries according to the level of monthly (Bulgaria and Romania) and guaranteed minimum allowances (Croatia), while the share of heating allowances decreased only in Romania, but is still very high. In all three countries the problem of energy poverty is present in 4 to 5 deciles. Additionally, the share of the population who consider that they cannot keep their homes warm is the biggest problem in Bulgaria (45%), then in Romania (14%) and Croatia (10%). Keywords: energy poverty, Bulgaria, Croatia, Romania JEL Classifications: Q48, I32